Sociodemographic, occupational, and personal factors associated with sleep quality among Chinese medical staff: A web-based cross-sectional study - Tian, Yusheng; Yue, Yuchen; Yang, Jiaxin; Chen, Hui; Wang, Jizhi; Liu, Junyu; Ding, Hui; Lu, Lulu; Zhou, Jiansong; Li, Yamin (Frontiers in Public Health, 2022)
Background: Sleep quality among medical staff affects not only their own health, but also the health of their patients. This study aimed to investigate the sociodemographic, occupational, and personal factors associated with sleep quality among medical staff in mainland China. Methods: An online survey was conducted from January 10 to February 5, 2019, involving 3684 medical staff (female:84.9%; mean age: 31.6 ± 7.7; age range:18-72). Sleep quality was measured by the Chinese version of the Pittsburgh Sleep Quality Index (C-PSQI). Sociodemographic, occupational characteristics and personal lifestyle factors were measured by standard questions. Multivariate logistic regression analyses were used to determine the factors associated with sleep quality. Results: 57.9% of the study population experienced poor sleep quality (C-PSQI>5). Associated factors of poor sleep quality were lower level of education, higher level of hospital care, longer weekly working hours, shift work, lack of regular naps or routine exercise and more than 30 minutes of cell phone use at bedtime. Conclusions: Poor sleep quality is highly prevalent among medical staff in mainland China. The findings indicate that appropriate strategies, such as implementing regular breaks, regulating overtime work and vacation interruptions, as well as developing exercise programs, relaxation training and stress-management programs could help improve the sleep quality of medical staff.